GREETING MESSAGE - INC 3 Nursing (UPT Penerbitan Universitas Jember, 2017)
Bismillahirrohmanirrohim Assalamualaikum Wr Wb Good morning and best wishes The Honorable, Rector of University of Jember The Honorable, Dean School of Nursing, University of Jember The Honorable, All Speaker of the International Nursing Conference The Honorable, Guests The Honorable, Conference Committee Dear All, All Participants of the conference Thank God we praise the presence of Allah SWT, because of the blessing and grace, we all can be present in this place, in order to attend the International Nursing Conference. Solawat and greetings may still be delegated to the Great Prophet Muhammad SAW. Ladies and Gentlemen, As the beginning of this speech, I would like to say welcome to the third international nursing conference, with the theme